2018
DOI: 10.1136/sextrans-2017-053443
|View full text |Cite
|
Sign up to set email alerts
|

Molecular test for chlamydia and gonorrhoea used at point of care in remote primary healthcare settings: a diagnostic test evaluation

Abstract: ObjectivesA new molecular test for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) (GeneXpert CT/NG) has been demonstrated to be as accurate as conventional nucleic acid amplification tests (NAAT), but performance has not been evaluated in routine primary care, performed at the point of care by clinicians. We aimed to examine its diagnostic performance when used by clinicians in remote community health services in Australia with high prevalences of CT and NG infection. The trial was registered with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…Several studies have shown that this can be used in settings with basic laboratory infrastructure. The utility of GeneXpert has been evaluated in remote populations such as an aboriginal community in Australia ; in routine antenatal care in Papua New Guinea (with STI rates by GeneXpert of CT 20%, NG 11.2% and TV 37.6%) ; in HIV‐infected pregnant women in South Africa (40.2% with STIs) . Another utility study in South Africa in HIV‐negative women presenting for STI care or with symptoms (CT 18.4%, NG 5.2%, TV 3%) resulted in STI testing of symptomatic and asymptomatic women and the same‐day treatment, with expedited partner treatment and reduced reinfection after six months .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that this can be used in settings with basic laboratory infrastructure. The utility of GeneXpert has been evaluated in remote populations such as an aboriginal community in Australia ; in routine antenatal care in Papua New Guinea (with STI rates by GeneXpert of CT 20%, NG 11.2% and TV 37.6%) ; in HIV‐infected pregnant women in South Africa (40.2% with STIs) . Another utility study in South Africa in HIV‐negative women presenting for STI care or with symptoms (CT 18.4%, NG 5.2%, TV 3%) resulted in STI testing of symptomatic and asymptomatic women and the same‐day treatment, with expedited partner treatment and reduced reinfection after six months .…”
Section: Resultsmentioning
confidence: 99%
“…The present work has certainly demonstrated that assay type can drive discordance, so specific evaluation of other and novel assays is warranted when considering whether (13). Clearly, POC testing does not rely on confirmation of the result at a reference laboratory, and growing interest in POC testing is evident in new technologies and quality processes to support this approach (14)(15)(16).…”
Section: Discussionmentioning
confidence: 88%
“…In keeping with our findings, the assay demonstrated a high sensitivity and specificity when performed by nurses and community health workers compared with conventional NAATs for both CT (98.6%, 99.5%) and NG (100%, 99.9%) using either urine samples or vaginal swabs. The authors concluded that this POC STI assay may be particularly suitable for LMICs, where resources are limited and infrastructure is often poor 9…”
Section: Discussionmentioning
confidence: 99%
“…These experiences by patients led to the study design, and the implementation of POC testing and EPT in the clinic. Patients took part in focus group discussions and were able to provide feedback to the study team on their experiences with the POC STI testing model 9…”
Section: Methodsmentioning
confidence: 99%